Pemberdayaan Kader Kesehatan Untuk Deteksi Dini Tuberkulosis Paru: Menjaga Kesehatan Masyarakat Melalui Aksi Preventif - Nur Triningtias P. (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study explores the role of contact investigation (CI) in detecting suspected tuberculosis (TB) cases in Babussalam District, Southeast Aceh Regency, in 2023. The focus is on empowering health cadres through simulation, practice, and mentoring in TB case investigation. A total of 20 health cadres were trained to conduct the investigation, resulting in tracing of 5 index cases, 57 households, and 217 individuals. Activities included case assessment, home visits, TB screening, education, mentoring, monitoring, and reporting. Recommendations encompass the application of knowledge and skills acquired by health cadres in TB management, while maintaining close coordination with local health centers and government authorities.